Determinants of scholarly project completion in a paediatric resident program in Canada. Issue 2 (28th June 2018) - Tien-Estrada, Joan; Vieira, Anajara; Percy, Vanessa; Millar, Kyle; Tam, Herman; Russell, Kelly; Crockett, Maryanne; Dart, Allison; McGavock, Jonathan
Abstract: Background: The primary aims of this study were to: 1) assess barriers and facilitators of completing scholarly projects from residents and faculty mentor perspectives, 2) determine the perceived value of new initiatives designed to support resident scholarly projects and 3) determine if these initiatives led to changes in resident publications. Design and Methods: Between June and September 2014, we surveyed 18 paediatric residents and 41 faculty mentors regarding barriers to resident scholarly project completion and the value of new initiatives to support scholarly activity. We also tracked scientific publications by residents before and after implementation of these initiatives. Results: The primary perceived barriers to research for residents and faculty were lack of protected time (64.3% versus 68.6%, respectively), lack of resident interest in scholarly activity (50.0% versus 60.0%, respectively) and lack of mentor motivation. Mentors and residents did not agree that lack of proper training in research (29% versus 54%, respectively) and faculty motivation (29% versus 17%, respectively) were barriers to completing a project. A dedicated research coordinator (71.4% versus 70.6%, respectively), a revised research curriculum (71.4% versus 41.2%, respectively) and works in progress sessions (50.0% versus 61.8%, respectively) were perceived as valuable initiatives to the program. These initiatives were not associated with changes in annual resident publication rates. Conclusions: Lack of time and competing clinical training are primary barriers to scholarly project completion for residents in addition to a lack of motivation on the part of faculty members. Improving program support was perceived as positive changes to address these barriers but did not increase resident publication rates. The information provided here could be used to tailor future resident research programs and highlight the value of gathering input from resident and faculty when designing initiatives to enhance resident research productivity.